Consensus clustering of gene expression profiles in peripheral blood of acute ischemic stroke patients - Yang, Zhiyong; Wang, Guanghui; Luo, Nan; Tsang, Chi Kwan; Huang, Li'an (Frontiers in Neurology, 2022)
Acute ischemic stroke (AIS) constitutes the primary cause of mortality and morbidity worldwide. Currently, no clinically approved immune intervention is available for AIS treatment, partly due to the lack of relevant patient classification based on peripheral immunity status of AIS patients. In this study, we adopted the consensus clustering approach to classify AIS patients into molecular subgroups based on the transcriptomic profiles of peripheral blood, and identified three distinct AIS molecular subgroups and 8 modules in each subgroup by the weighted gene co-expression network analysis. Remarkably, the pre-ranked gene set enrichment analysis revealed that the co-expression modules with subgroup I-specific signature genes were significantly overlapped with the differentially expressed genes in AIS patients with hemorrhagic transformation (HT). With respect to subgroup II, exclusively male patients with decreased proteasome activity were identified. Intriguingly, the majority of subgroup III was composed of female patients who showed comparatively lower level of AIS-induced immunosuppression (AIIS). In addition, we discovered a nonlinear relationship between female age and subgroup-specific gene expression, suggesting a gender- and age-dependent alteration of peripheral immunity. Taken together, our novel AIS classification approach could facilitate immunomodulatory therapies including the administration of gender-specific therapeutics, attenuation of the risk of HT and AIIS after ischemic stroke.